Bali – Massentourismus und nachhaltige Entwicklung: Die sozio-ökonomische Dimension - Vorlaufer, Karl (ERDKUNDE, 1999)
Bali is one of the most important destinations for Third World tourism. The Balinese’s way of life is increasingly affected by mass tourism. Especially ecological and cultural aspects of sustainable development are endangered: by disturbing the intact environment and the Balinese culture tourism might destroy its own basis. This paper proposes that a long-term protection of ecological and cultural resources is possible only if the Balinese can profit from the economic benefits generated by tourism. This will only be possible if they are willing and also economically able to protect their resources. This paper shows that tourism makes a major contribution to Bali's economy. During the last few years the average income, the number of jobs, and the foreign exchange receipts have rapidly increased. Bali which was an economic problem region in Indonesia before tourism developed has turned into a quite prosperous island. This rapid development in tourism was only made possible by the massive investments of non-Balinese sources, especially those from Java, but also foreign ones. Thus, Bali's tourist economy can be regarded as being heavily externally controlled. On the long run sustainable development my be threatened. Furthermore, tourism has led to increased spatial disparities in Bali. Land use conflicts in the urbanized coastal regions of the southern part of the island have been intensified. Tourism's great need for space has led to its expansion into areas of wet rice cultivation which are not only attractive destinations for tourists, but also essential parts of Bali's economy and cultural identity. In connection with the concentration of settlements in central South Bali, mainly influenced by tourism, this could lead to the destruction of essential resources for tourism and endanger sustainable development.